2000
DOI: 10.1055/s-2000-10128
|View full text |Cite
|
Sign up to set email alerts
|

Die intraoperative Hyperpyrexie bei Osteogenesis imperfecta-Betroffenen

Abstract: The aim of this study was to evaluate the influence of different types of anesthesia upon the intra- and postoperative body temperature in osteogenesis imperfecta patients. The development of an intraoperative hyperpyrexia of unknown origin is a typical phenomenon in patients with osteogenesis imperfecta. Body temperatures of up to 40 degrees C are known to complicate the operation. Therefore, in a retrospective study, the pre-, intra- and postoperative body temperature curves of 45 operations under different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…It is unknown if the hyperthermia was specific to this patient or whether other de Barsy syndrome patients may be affected, as in other congenital syndromes. Nonmalignant hyperthermia has been reported in other congenital syndromes such as osteogenesis imperfecta and Costello syndrome [14,15]. It has also been described in patients undergoing bidirectional Glenn procedures and protracted eye operations involving high atropinization [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…It is unknown if the hyperthermia was specific to this patient or whether other de Barsy syndrome patients may be affected, as in other congenital syndromes. Nonmalignant hyperthermia has been reported in other congenital syndromes such as osteogenesis imperfecta and Costello syndrome [14,15]. It has also been described in patients undergoing bidirectional Glenn procedures and protracted eye operations involving high atropinization [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…More recent publications suggest that the hypermetabolic state and hyperthermia observed in OI during the perioperative period are not MH because they are self-limiting, muscle rigidity is not seen, and normocarbia is maintained. It is more likely that this phenomenon is a disorder of central thermoregulation, which can be triggered by various factors [2,9,12].…”
Section: Discussionmentioning
confidence: 99%
“…Fuerderer et al [12] reported 45 anaesthetics in 22 children with OI. In 27 procedures, balanced anaesthesia was administered using fentanyl and enflurane, while in 18 procedures, total intravenous anaesthesia (TIVA) was administered using propofol and alfentanil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unter Narkose kann es dann zu einem Hypermetabolismus kommen, der häufig mit schweren Komplikationen verbunden ist [9]. Auch hier könnten die volatilen Anästhetika eine Triggerfunktion besitzen [5]. Die Durchführung totaler intravenöser Anästhesien stellt heutzutage keinerlei Probleme mehr da, sodass generell empfohlen werden kann, triggerfreie Narkosen durchzuführen.…”
Section: Disposition Zur Malignen Hyperthermieunclassified